PEMANFAATAN LIMBAH FLY ASH DAN ZEOLITE PADA AKTIVASI KIMIA DENGAN TAMBAHAN SUPERPLASTICIZER SEBAGAI BAHAN PENGGANTI SEMEN PADA BETON GEOPOLYMER - Siska Apriwelni; Ahmad Yudi; Nugraha Bintang Wirawan; Kirtinanda P; Muhammad Abi Berkah Nadi; Siti Rahma; Hendrawan Hendrawan (Racic : Rab Construction Research, 2025)
The increasing production of Portland cement contributes significantly to global warming; therefore, the utilization of Fly Ash waste and natural Zeolite as alternative binders in concrete production is worth considering. This research was conducted experimentally using class F Fly Ash as the primary binder with Natural Zeolite substitutions of 0%, 5%, 10%, 15%, and 20%. The activators employed were NaOH 10M and Na₂SiO₃ with a ratio of 1:2 for Fly Ash, and NaOH 1M and HCl 1M for Zeolite. Tests included compressive strength, unit weight, and slump test on cylindrical specimens cured for 28 days. The results showed that a 15% Zeolite substitution achieved the optimum compressive strength of 34.80 MPa (NaOH 1M) and 33.74 MPa (HCl 1M), representing a 28.13% and 24.22% increase compared to GPC NZ 0%. The unit weight of geopolymer concrete was generally lower than that of normal concrete but increased with higher Zeolite content. In terms of cost, geopolymer concrete was 36.51% more expensive than normal concrete; however, its improved mechanical performance and physical properties make the Fly Ash–Zeolite combination a viable and environmentally friendly binder alternative